(untitled) - Mulgan, Aurelia George (Canberra, 2002)
This book explains why the process of economic reform in Japan is so problematic, and why reviving Japan’s economy is proving so difficult. It offers a new explanation for Japan’s failure to reform in terms of what is identified as Japan’s "party-bureaucratic government" which undermines the power of the Prime Minister and in which forces opposed to reform are embedded. It concludes that achieving economic reform will require that Japan first reform its policymaking system to give sufficient power to the executive in order to override the ruling party.